Study on the Precision Supply Mechanism of Smart Community Elderly Care Services Empowered by Digital Technology - Fu, Yangfang (International Journal of Social Sciences and Public Administration, 2025)
The empowerment of digital technology injects new momentum into the digital supply of smart community elderly care services and facilitates the deep restructuring of service scenarios, technological embedding, and governance frameworks. The precision supply of smart community elderly care services enabled by digital technology follows a practical logic centered on "technology embedding-platform-based decision-making-data-driven operation-collaborative co-governance." The realization of such precision supply depends on the synergistic support among multiple elements, including governance coordination capacity, data resource foundations, user adaptability, scenario application infrastructure, and institutional safeguards. To enhance the effectiveness of digitally empowered precision supply in smart community elderly care, it is essential to continuously improve the mechanisms for collaborative governance, data governance, technological empowerment, integrative participation, and evaluative feedback.